Nicaragua dairy systems dynamics model – public facing aspect - CGIAR Research Program on Livestock (2018)
The value chain model is fully operational, with public interface hosted online. Two papers from this project, have been completed. This combination of stakeholder-led model building and public model hosting is currently being followed and scaled out in two on-going bilateral funded projects in Bihar and Bangladesh